The relationship between Iranian EFL Learners' multiple intelligence and listening strategies - Heidari, Farrokhlagha; Panahandeh, Essa (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The purpose of the current study was to identify the most and the least frequently used types of multiple intelligences (MIs) and listening strategies of the Iranian EFL learners, to examine the relationship between multiple intelligences types as a whole factor and listening strategies, and to investigate the effect of gender on the use of different types of multiple intelligences and listening strategies. To this end, a 90-item multiple intelligence questionnaire and a 23-item listening strategy questionnaire were distributed among 120 Iranian male and female EFL learners from the universities of Sistan and Baluchestan, Iranshahr, and Yasuj. Descriptive statistics (mean and standard deviation), and inferential statistics (correlation and independent t-test) were used to analyze the data. The data analyses demonstrated that the most and the least dominant types of multiple intelligences among participants of this study were existential and naturalistic intelligences and those of listening strategies were cognitive and socio-affective strategies, respectively. The results also revealed that there was some significant positive relationship between the overall MIs and listening strategies. In a similar vein, the findings indicated that there are significant differences between male and female students in bodily, interpersonal, and existential intelligence, but the analysis showed no significant difference between male and female students regarding their listening strategies.